Genome-wide association study identified candidate genes controlling continuous storage root formation and bulking in hexaploid sweetpotato - Bararyenya, Astère; Olukolu, Bode A.; Tukamuhabwa, Phinehas; Grüneberg, Wolfgang J.; Ekaya, Wellington; Low, Jan; Ochwo-Ssemakula, Mildred; Odong, Thomas L.; Talwana, Herbert; Badji, Arfang; Kyalo, Martina; Nasser, Yao; et al. (BMC plant biology, 2020)
Continuous storage root formation and bulking (CSRFAB) in sweetpotato is an important trait from agronomic and biological perspectives. Information about the molecular mechanisms underlying CSRFAB traits is lacking. Results: Here, as a first step toward understanding the genetic basis of CSRFAB in sweetpotato, we performed a genome-wide association study (GWAS) using phenotypic data from four distinct developmental stages and 33,068 single nucleotide polymorphism (SNP) and insertion-deletion (indel) markers. Based on Bonferroni threshold (pvalue < 5 × 10− 7), we identified 34 unique SNPs that were significantly associated with the complex trait of CSRFAB at 150 days after planting (DAP) and seven unique SNPs associated with discontinuous storage root formation and bulking (DCSRFAB) at 90 DAP. Importantly, most of the loci associated with these identified SNPs were located within genomic regions (using Ipomoea trifida reference genome) previously reported for quantitative trait loci (QTL) controlling similar traits. Based on these trait-associated SNPs, 12 and seven candidate genes were respectively annotated for CSRFAB and DCSRFAB traits. Congruent with the contrasting and inverse relationship between discontinuous and continuous storage root formation and bulking, a DCSRFAB-associated candidate gene regulates redox signaling, involved in auxin-mediated lateral root formation, while CSRFAB is enriched for genes controlling growth and senescence. Conclusion: Candidate genes identified in this study have potential roles in cell wall remodeling, plant growth, senescence, stress, root development and redox signaling. These findings provide valuable insights into understanding the functional networks to develop strategies for sweetpotato yield improvement. The markers as well as candidate genes identified in this pioneering research for CSRFAB provide important genomic resources for sweetpotato and other root crops.
Keywords: DArTseq; Genotyping-by-sequencing; GWAS; CSRFAB; GBSapp; Polyploid; SNPs; Sweetpotato